2004
DOI: 10.1161/01.str.0000106763.46123.f6
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Effect of Aspirin in Patients With Cerebrovascular Disease

Abstract: Background and Purpose-Aspirin is used commonly to prevent ischemic strokes and other vascular events. Although aspirin is considered safe and effective, it has limited efficacy with a relative risk reduction of 20% to 25% for ischemic stroke. We sought to determine if aspirin as currently used is having its desired antiplatelet effects. Methods-We ascertained patients with cerebrovascular disease who were taking only aspirin as an antiplatelet agent.Platelet function was evaluated using a platelet function an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
3
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(103 citation statements)
references
References 27 publications
6
91
3
3
Order By: Relevance
“…It would be important to repeat this study with assays of platelet inhibition. It should be noted however that studies using urinary or serum thromboxane levels, or the Platelet Function Assay-100 have found a dose response with low vs. higher doses of aspirin, which lend support to our observations [19][20][21][22][23][24] although both these methods, also have significant limitations themselves.…”
Section: Discussionsupporting
confidence: 83%
“…It would be important to repeat this study with assays of platelet inhibition. It should be noted however that studies using urinary or serum thromboxane levels, or the Platelet Function Assay-100 have found a dose response with low vs. higher doses of aspirin, which lend support to our observations [19][20][21][22][23][24] although both these methods, also have significant limitations themselves.…”
Section: Discussionsupporting
confidence: 83%
“…There are some data suggesting an association between severity and frequency of acute vascular events and poor platelet response after ASA in patients with coronary artery disease [5]. A high prevalence of ASA resistance (28.0–65.0%) was also demonstrated among poststroke ASA users [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous studies reported that the antiplatelet effect of ASA is diminished in many patients with cerebrovascular disease, ranging from 5 to 60% [7,8,9,10,11,12,13], a problem colloquially termed ‘aspirin resistance’ [13,14,15]. Such variability in the extent of platelet inhibition by ASA may also reflect the use of various nonstandardized laboratory assays and suggests that one single platelet function test may not allow a general definition of ASA hypo- or nonresponse [16].…”
Section: Introductionmentioning
confidence: 99%